Moral Ekonomi Orang Bali Di Kelurahan Martajaya Kecamatan Pasangkayu Kabupaten Pasangkayu - Rahayu, Afifa Putri; Kesuma, Andi Ima (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This study aims to know and understand the cultural values ​​that exist in the Martajaya sub-district, to know and understand the morals and economy of the people in the Martajaya sub-district and to know and understand the work ethic of the people who live in the Martajaya sub-district. To achieve this goal, a qualitative research method was adopted by means of observation, interviews and documentation. The data that has been obtained is then analyzed and interpreted based on relevant theories and research results. The results of the study show that traditional values ​​in the belief tradition, Hindu religious rituals, and the human life cycle are inherited from their predecessors where the people in the Martajaya sub-district are transmigrants from the island of Bali who have never left the traditions below them from the village. Page. As for the morals of the people in the Martajaya sub-district, they are very well instilled. This is what makes the sub-district so peaceful when we visit the Martajaya sub-district. From an economic point of view, the community’s success in developing its economy can be proven by building a magnificent temple and that reflects how rich the person is. People see that if the temple or place of worship is large, then the owner is a rich or respected person. To improve their economy, the people in the Martajaya sub-district do not only work as oil palm fruit farmers but also take opportunities in the entrepreneurial field such as opening a shop for mixed ingredients for daily needs, photocopying and others.